Causal Modelling of the Key Competitiveness Assessment Factors of Wellness Tourism Destinations: A DEMATEL Approach - Thadathibesra Phuthong; Pongpun Anuntavoranich; Achara Chandrachai; Krerk Piromsopa (Journal of Human, Earth, and Future, 2023)
Objectives: The objectives of this study are 1) to identify and prioritize the significant competitiveness factors that need to be considered in the context of wellness tourism destinations and 2) to identify the causal interrelationships between competitiveness factors that need to be considered in the context of wellness tourism destinations. Methods/Analysis: The theoretical framework of this research began with documentary research of secondary data, followed by semi-structured interviews and quantitative research using questionnaires to collect primary data from wellness tourism clusters and experts. Based on these responses, a multiple-criteria decision-making framework using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was implemented to prioritize wellness tourism destination competitiveness factors and their relationships. Findings: The destination strategy and roadmap for wellness tourism were the most important competitiveness factors for wellness tourism destinations, and the wellness service experience and activities factor was the most significant cause factor, with strategies to improve service and restoration being the most significant source of effect. Novelty/Improvement:This research sheds light on wellness tourism destinations' competitiveness assessment factors and indicators and how to improve them to attract wellness tourists seeking preventive health care or health promotion services.